Oliver and Amanda's Halloween - Van Leeuwen, Jean.; Schweninger, Ann (New York : Dial Books for Young Readers, 1992)
Oliver and Amanda Pig's Halloween activities include making their costumes, getting a pumpkin for a jack-o'-lantern, and going trick-or-treating.
"Reading level 2.0"--T.p. verso.
School Library Journal
Publisher's Weekly
Booklist
1.8
K-3
Keywords: Halloween -- Fiction; Pigs -- Fiction; Brothers and sisters -- Fiction; Halloween -- Fiction; Pigs -- Fiction; Brothers and sisters -- Fiction